1989
DOI: 10.1093/nar/17.15.6409
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of a cDNA specifying subunit VIa of human cytochromecoxidase

Abstract: Cytochrcae c cxcidase (COX; EC 1.9.3.1) catalyzes the transfer of electrons fra reduced cytochran c to uolecular aoygen in the mitochdrial respirtory diain. In mmnamls, the apoprotein is ccmposed of three larger catalytic suimits, encoded by the tc ria genrupx, and by ten smaller, nmclear-e ded submnits, which may play a reulatory role (1); subunits VIa, VIIa, and VIII have been shown to have heart-and liver-specific isoforms in cows and pigs (2), and c[s encoding the heart-and liver-specific isoforms of sub.u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The CG17280 gene is an ortholog of the human COX subunit VIa precursor (Fabrizi et al 1989). Sequencing of CG17280 DNA in the levy 1 mutant revealed a G-to-A transition occurring at the 39-splice junction of the single intron ( Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The CG17280 gene is an ortholog of the human COX subunit VIa precursor (Fabrizi et al 1989). Sequencing of CG17280 DNA in the levy 1 mutant revealed a G-to-A transition occurring at the 39-splice junction of the single intron ( Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…For analysis of nuclear transcripts, human cDNA probes for the following subunits of COX were used: IV [38], Va [39], Vb [40], liver type of VIa (VIaL) [22] and of VIIa (VIIaL) [26], heart type of VIa (VIaH) [23] and VIIc [41], all kindly provided by Dr E. A. Schon. A bovine cDNA probe was used to analyse transcripts of subunit VIIb [42] (a kind gift of Dr R. A. Capaldi).…”
Section: Probesmentioning
confidence: 99%
“…In rat only the L form of subunit VIIa was found [17, 181, but both isoforms of subunits VIa [ l l ] and VIII [19]. In human, subunit VIII is present only in the L form [20,211, whereas both isoforms occur for subunits VIa [22,. Most of the other nuclearcoded subunits have been cloned and sequenced from rat, beef and human (for review see [28,291).…”
mentioning
confidence: 99%
“…Va, human Va, rat (Droste et ai., 1989) Vlb, human (Taanman et ai., 1989) Vlb, beef (Lightowlers & Capaldi, 1989) IV, human (Zeviani et al, 1987) IV, rat (Gopdan et al, 1989) IV, beef (Lomax et ai., 1984) Vla, human L (Fabrizi et al, 1989) Vla, rat H Vlc, human (Otsuka et al, 1988) Vlc, rat (Suske et al, 1987) Vllb, beef (Lightowlers et al, 1989) VIII, human (Rizzuto et al, 1989) VIII, beef L (Lightowlers et al, 1990) VIII sequences shown in capital letters and mature sequences given in lower case letters.…”
Section: Mlgaalrrcavattradrrgllhsartpgpavaiqsvrcy-mlaaalrrct--taaaaarmentioning
confidence: 99%